Unified programs nationally? Strengths and weaknesses of the learning standards - Polo Martínez, Ignacio (Avances en Supervisión Educativa, 2014)
The inclusion of measurable learning standards as an element of the curriculum has definitely opened the door to the connection between the curriculum and external assessments. Since its origin, the potential impact of that element in improving our educational system has been defended and criticized. The truth is that in our country, though all regions are based on the same Royal Decree of core curriculum, and therefore the same reference for the evaluation, curriculum that ultimately applies to students ( teaching-learning- assessment ) from the different regions can have significant differences . This article proposes, from the analysis of various research , training programs, the plan of action for inspection and the author's own experience in processes of curriculum specifications , assess the potential strengths and weaknesses of the learning standards.
Keywords: attention to diversity; assessment; standards; instruments